Determinants of organizational culture that influence innovation. The case of production companies in Poland - Strychalska-Rudzewicz, A. (Видавництво Львівської політехніки, 2014)
The purpose of this paper is to present the results of a study aimed at identifying factors of organizational culture that influence innovation of enterprises, as well as to determine the strength of this effect. The foremost and most crucial statistical correlation has been noticed between the innovativeness of a company and the introduction of innovation in the company’s mission and vision, creativity of employees, strong commitment to work, open communication and good flow of information, the image of the company, regular work on innovation, competitiveness as a priority, use of information technology in the flow of information and decision-making in the innovation process. The research shows that the number of product innovations implemented (brand new and upgraded) and process innovations (brand new and upgraded) increases together with the enterprise size. Подано результати дослідження, спрямованого на визначення факторів організаційної культури, які впливають на інновації підприємств, а також визначення сили цього впливу. Найвагомішу статистичну кореляцію виявлено між інноваційністю компанії та впровадженням інновацій в місію і візію компанії, творчість працівників, наполегливість у роботі, відкрите спілкування та відмінний інформаційний потік, імідж компанії, регулярну роботу над інноваціями, конкурентоспроможність як пріоритет, використання інформаційних технологій в потоці інформації та прийняття рішень інноваційному процесі. Дослідження показують, що кількість реалізованих продуктових інновацій (нові та вдосконалені бренди) і процесних інновації (нові та вдосконалені) збільшуються разом з розміром підприємства.
Фактори організаційної культури, які впливають на інновації. Приклад виробничих підприємств у Польщі
Keywords: innovation; culture; determinants; інновації; культура; детермінанти